Aggressive Pharmacotherapy in Reproductive Medicine. Pregnancy and Medicines (Author's Perspective) - V. E. Radzinskiy (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2024)
The article discusses the issues of polypharmacy and unjustified prescribing in pregnant women. The author- Honoured Scientist of the Russian Federation, Corresponding Member of the Russian Academy of Sciences, Doctor of Medical Sciences, Full Professor, and Head of the Department for Obstetrics and Gynaecology with a Course on Perinatology at the Institute of Medicine of the Peoples' Friendship University of Russia named after Patrice Lumumba, Viktor E. Radzinskiy - questions the established practice of unnecessary hospitalisation of pregnant women without clinical indications and prescribing them numerous medicinal products, including antimicrobials, hormones, and antispasmodics. In most cases, pregnancy does not require medical intervention. The widespread use of progestogens in patients with threatened miscarriage lacks an evidence base. Antispasmodics, such as papaverine, are ineffective in threatened preterm labour. The author calls for a rational approach to prescribing medicinal products to pregnant women based on current clinical practice guidelines and the "do no harm" maxim. Viktor E. RADZINSKIY emphasises the need to follow clinical protocols and ensure physicians are informed about the evidence for the use of medicinal products in pregnancy to prevent polypharmacy and adverse consequences.